2024 Consolidated Technical and Financial Report for Independent Advisory and Evaluation Service (IAES), Independent Science for Development Council (ISDC), and Standing Panel on Impact Assessment (SPIA) - Independent Advisory and Evaluation Service (2025)
Within CGIAR, the Independent Advisory and Evaluation Services (IAES) provides operational support as the secretariat for the Independent Science for Development Council (ISDC) and the Standing Panel on Impact Assessment (SPIA), and it implements CGIAR’s multi-year, independent evaluation plan as approved by the CGIAR System Council. As such, this report compiles the 2024 summary technical and financial reporting for each of these areas, i.e., both supported independent bodies and the evaluation activities conducted under the auspices of IAES. The report opens with reporting on the two independent supported bodies (ISDC and SPIA), then covers the independent evaluation activities, and concludes with operational support.